Determination of Total Flavonoid Content of the n-Hexane Fraction of Gelinggang Leaf Extract by UV-Vis Spectrophotometric Method - Satria, Romi; Hakim, Ali Rakhman; Darsono, Putri Vidiasari (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Indonesia memiliki kekayaan alam yang berlimpah, yang dimanfaatkan sebagai obat tradisional untuk masyarakat. Daun Gelinggang (Senna alata L) memiliki aktivitas antijamur berdasarkan senyawa metabolit sekunder berupa flavonoid, saponin, tanin steroid, alkaloid yang diharapkan dapat menjadi alternativ lain dalam pengobatan antijamur. Tujuan penelitian ini adalah untuk menganalisis kadar flavonoid total dari fraksi Daun Gelinggang dengan metode spektrofotometri UV-Vis. Penelitian ini menggunakan Analisis kualitatif mengidentifikasi senyawa flavonoid sedangkan analisis kuantitatif untuk menentukan kadar flavonoid menggunakan spektrofotometri uv-vis yang akan diperoleh nilai dari absorbansi dimasukkan ke dalam persamaan regresi linear yaitu y = bx + a yang diperoleh dari kurva kalibrasi perbandingan dan hasil dinyatakan dalam satuan mg/gram dan persen. Hasil penelitian dari identifikasi uji warna shinoda pada ekstrak daun gelinggang positif mengandung flavonoid yang berwarna hijau lumut dan penetapan kadar flavonoid total dari daun gelinggang sebesar 2,563%. Dari penelitian ini dapat disimpulkan bahwa fraksi n-heksana memiliki kadar flavonoid sebesar 2,563%. Determination of Total Flavonoid Content of the n-Hexane Fraction of Gelinggang Leaf Extract by UV-Vis Spectrophotometric Method Abstract: Indonesia has abundant natural resources, which are used as traditional medicine for the community. Gelinggang leaf (Senna alata L) have antifungal activity based on secondary metabolites in the form of flavonoids, saponins, steroid tannins, and alkaloids which are expected to be other alternatives in antifungal treatment. The research objective is to analyze the total flavonoid content of the Gelinggang Leaf fraction using the UV-Vis spectrophotometry method. This study used qualitative analysis to identify flavonoid compounds and quantitative analysis to determine flavonoid levels using UV-Vis spectrophotometry. The absorbance value obtained is entered into the linear regression equation, namely y = bx + a from the comparison calibration curve and the results are expressed in units of mg/gram and percent. The results of the identification of the Shinoda color test on Gelinggang leaf extract were positive for moss-green flavonoids and the determination of the total flavonoid content of Gelinggang leaf was 2.563%. From this study, it can be concluded that the n-hexane fraction has a flavonoid content of 2.563%. Keywords: Gelinggang Leaf, N-hexane Fraction, Total Flavonoid Content, UV-VIS Spectrophotometry Method.